Does the Expansion of Public Long-Term Care Funding Affect Savings Behaviour? - Joan Costa-i-Font; Cristina Vilaplana (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the effect of further public caregiving subsidies (and insurance expansions to cover long-term care) on savings and saving behaviour. Specifically, weexamine the unique progressive introduction of a universal public long-term care subsidy (Sistema para la Autonomía y Atención a la Dependencia, SAAD) in Spain. We draw on a difference-in-difference strategy (DID) to show a contraction of savings after the policy intervention, but only among younguer elders who receive primarily cash benefits (unconditional caregiving allowance) as opposed to home help (ranging between 13% and 38% of the subsidy ammount). Saving reductions of individuals in the second and third quintile of income distribution, those without children and those residing in regions that implemented the reform earlier, drive the effect.
Keywords: I18; D14; G22; 330; long-term care insurance; savings; saving behaviour; long term care services and support; universalisation; Spain